EuroArte '89. - EuroArte Guimaraes 1989 (Guimaraes : EuroArte, 1989)
Smith, Richard ; Hockney, David ; Witkin, Isaac ; Jones, Allen ; Annesley, David ; Tilson, Joe ; Donaldson, Anthony ; Blake, Peter ; Caulfield, Patrick ; Boshier, Derek ; Phillips, Peter ; Beuys, Joseph ; Basso, Dario Alvarez ; Rufo, Manuel ; van Berner, Darya ; Gomez, Maria ; Fernandez, Maria Luisa ; Barcelona, Jordi Colomer ; etc.
boek